HLA-C Incompatibilities in Allogeneic Unrelated Hematopoietic Stem Cell Transplantation - Tiercy, Jean-Marie (Frontiers in Immunology, 2014)
An increasingly larger fraction of patients with hematological diseases are treated by hematopoietic stem cells transplantation (HSCT) from HLA matched unrelated donors. Polymorphism of HLA genes represent a major barrier to HSCT because HLA-A,B,C and DRB1 incompatibilities confer a higher risk of aGVHD and mortality. Although >22 million volunteer HLA-typed donors are available worldwide, still a significant number of patients do not find a highly matched HSC donor. Because of the large haplotypic diversity in HLA-B-C associations, incompatibilities occur most frequently at HLA-C, so that unrelated donors with a single HLA-C mismatch often represent the only possible choice. The ratio of HLA-C-mismatched HSCT over the total number of transplants varies from 15-30%, as determined in 12 multicenter studies. Six multicenter studies involving >1800 patients have reported a 21-43% increase in mortality risk. By using in vitro cellular assays a large heterogeneity in T-cell allorecognition has been observed. Yet the permissiveness of individual HLA-C mismatches remains poorly defined. It could be linked to the position and nature of the mismatched residues on HLA-C molecules, but also to variability in the expression levels of the mismatched alleles. The permissive C*03:03-03:04 mismatch is caracterized by full compatibility at residues 9, 97, 99, 116, 152, 156 and 163 reported to be key positions influencing T-cell allorecognition. With a single difference in these key residues the C*07:01-07:02 mismatch might also be considered by analogy as permissive. High variability of HLA-C expression as determined by quantitative RT-PCR has been observed within individual allotypes and shows some correlation with A-B-C-DRB1 haplotypes. Thus in addition to the position of mismatched amino acid residues, expression level of patient’s mismatched HLA-C allotype might influence T-cell allorecognition, with patient's low expression-C alleles representing possible permissive mismatches.